Evolution of Dry/Wet Climate in Xichang from 1961 to 2016 - XIAO Xiwen; ZHANG Yunlu; LIU Chunhong; WANG Yuefeng (Renmin Zhujiang)
Regional climate analysis can optimize and supplement global climate research,and it is of vital significance for predicting regional climate changes and extreme weather.Based on the daily temperature and precipitation data from 1961 to 2016 in Xichang city,this paper systematically reveals the characteristics of temperature,precipitation,and dry and wet climate changes at annual and inter-annual scales by using the cumulative anomaly method,nonparametric trend analysis of time series (innovative trend analysis (ITA) method and ITA-change boxes (ITA-CB) method) and standardized precipitation evaporation index (SPEI).The results show that:① The distribution characteristics of annual temperature and precipitation in Xichang are similar,with the maximum value of both appearing in July.Moreover,the minimum temperature and precipitation appear in January and February,respectively.The average inter-annual and inter-decadal temperatures increase obviously,and the average inter-decadal precipitation improves slowly.② For the past 56 years,Xichang has witnessed apparent dry and wet climate changes.SPEI has dropped in a fluctuating tendency.In addition,it is negatively correlated with temperature (p<0.05) but positively correlated with precipitation (p<0.01).As temperature increases significantly,the drought degree has become more and more serious since 2003,and the negative value of SPEI accounts for 78.6%.The proportion of drought to extreme drought has increased to 28.6% in 2010.③ The average annual precipitation increases in low-value regions but decreases in high-value regions.The average annual temperature rises both in low-value regions and high-value regions and basically maintains an increasing tendency in median regions.SPEI increases in low-value regions but decreases in median and high-value regions.The research results can provide a reference for Xichang in dealing with climate change and formulating disaster prevention and mitigation plans.